Vocabulario Tagalo Tagalog-Spanish dictionary - San Antonio, Francisco de d.1624; Postma, Antonio 1943-. (Quezon City Pulong Sources for Philippine Studies, 2000)
A Tagalog-Spanish dictionary which is a reconstruction of the original manuscript of the early Tagalog-Spanish dictionary during the colonial era. This dictionary contains 7,000 entry words.
A reconstruction of a manuscript form compiled in Laguna sometime before 1620.
Jointly published with Ateneo de Manila University.
Keywords: Tagalog language -- Spanish. -- Dictionaries; Spanish language -- Tagalog. -- Dictionaries